2011
DOI: 10.1002/ase.262
|View full text |Cite
|
Sign up to set email alerts
|

Optical versus virtual: Teaching assistant perceptions of the use of virtual microscopy in an undergraduate human anatomy course

Abstract: Many studies that evaluate the introduction of technology in the classroom focus on student performance and student evaluations. This study focuses on instructor evaluation of the introduction of virtual microscopy into an undergraduate anatomy class. Semi-structured interviews were conducted with graduate teaching assistants (TA) and analyzed through qualitative methods. This analysis showed that the teaching assistants found the virtual microscope to be an advantageous change in the classroom. They cite the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…All studies assessing P e for both TL and NTL did so subjectively via surveys, questionnaires, interviews or observations. The large majority of these studies (n ¼ 25, 86%) focused only on student P e , but a small number of them (n ¼ 2, 7%), such as Collier et al (2012) and Gorghiu et al (2009), focused on instructor P e . An additional 7% (n ¼ 2) of studies (Rajendran, Veilumuthu, & Divya, 2010;Scott, 2009) assessed both student and instructor P e .…”
Section: Perception (P E )mentioning
confidence: 97%
See 2 more Smart Citations
“…All studies assessing P e for both TL and NTL did so subjectively via surveys, questionnaires, interviews or observations. The large majority of these studies (n ¼ 25, 86%) focused only on student P e , but a small number of them (n ¼ 2, 7%), such as Collier et al (2012) and Gorghiu et al (2009), focused on instructor P e . An additional 7% (n ¼ 2) of studies (Rajendran, Veilumuthu, & Divya, 2010;Scott, 2009) assessed both student and instructor P e .…”
Section: Perception (P E )mentioning
confidence: 97%
“…Only 9% (n ¼ 2) of those studies (Chan & Fok, 2009;Collier, Dunham, Braun, & O'Loughlin, 2012) assessed P e alone. All studies assessing P e for both TL and NTL did so subjectively via surveys, questionnaires, interviews or observations.…”
Section: Perception (P E )mentioning
confidence: 98%
See 1 more Smart Citation
“…They found that such a virtual teaching environment can significantly improve practical operation ability and motivation of the participants. Some researchers have applied virtual teaching technology in college anthropotomy classes, created virtual microscopes for teaching, and considered virtual teaching technology as a beneficial teaching technique for increasing students' interest in learning [4].…”
Section: Introductionmentioning
confidence: 99%
“…With an appropriate bandwidth, virtual microscopes can be used simultaneously by a large number of people, thereby surpassing the restrictions related to a limited number of CLMs in a laboratory [4,9,12,16,17] and stimulating cooperation between students [9,12,15,17,18,19]. Moreover, the interaction between teachers and students is improved by viewing the same image at the same time in the classroom, which allows bringing up questions easily and improves the learning curve [15,18,19]. …”
Section: Advantages Of Wsimentioning
confidence: 99%